2017
DOI: 10.18203/2320-6012.ijrms20174001
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal outcome in women with gestational diabetes mellitus

Abstract: Objective: The aim of this study was to assess the fetomaternal outcome in patients with gestational diabetes mellitus.Methodology: This study was conducted in the department of obstetrics and gynecology GMC Srinagar. Patients with period of gestation more than 28 weeks with Gestational Diabetes Mellitus were included in study group and 100 non diabetic patients with similar period of gestation were taken as controls. Risk factors and fetomaternal outcome was compared in the two groups.Results: Gestational dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…This may be attributed to the increased level of insulin resistance, high levels of circulating a dipokines and inflammatory markers, and oxidative stress may be responsible for this association. 13 Mean BMI in the study population was found to be 23.28±3.61 kg/m 2 and for GDM population was 28±5.14 kg/m 2 . The prevalence of GDM increased with BMI (P=0.007).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This may be attributed to the increased level of insulin resistance, high levels of circulating a dipokines and inflammatory markers, and oxidative stress may be responsible for this association. 13 Mean BMI in the study population was found to be 23.28±3.61 kg/m 2 and for GDM population was 28±5.14 kg/m 2 . The prevalence of GDM increased with BMI (P=0.007).…”
Section: Discussionmentioning
confidence: 70%
“…This is consistent with the findings by Nayak et al, 10 as women with GDM were older as compared to the non-GDM women (25.67 vs. 24.24, P=0.08); however, difference was not significant. Song et al, 11 also found that women with GDM were significantly higher in age than those 13 found that there were significantly more women with GDM in >35 years age group than those without GDM (21 vs. 9, P=0.004955). Advanced maternal age is reported to be an independent risk factor for GDM.…”
Section: Discussionmentioning
confidence: 90%
“…2 of the births for the GDM group were stillbirths. (11) , 86% of the GDM group mothers were at risk based on their age over 25 years and overweight concluding that proper screening and early knowledge of the risk factors does play a humungous role in reducing maternal and fetal complications in Gestational Diabetes Mellitus.…”
Section: Primi Multimentioning
confidence: 99%
“…6 Fetal complications likely to develop are macrosomia, IUD, malformation includes anencephaly, spina bifida, transposition of great vessels, VSD, renal agenesis, caudal regression syndrome, RDS, hypoglycemia, hypothermia, hyperbillirubinemia, hypocalcemia, hyperviscicity. 7 Maternal complications includes a) Antepartam:…”
Section: Introductionmentioning
confidence: 99%